The Pathophysiology of Skin Failure vs. Pressure Injury: Conditions That Cause Integument Destruction and Their Associated Implications - Bain, Michael; Hara, Junko; Carter, Marissa J (Wounds (King of Prussia, Pa.), 2020)
Although integument failure commonly is attributed to pressure alone, especially when a wound develops over a bony prominence (pressure injury), all skin failure should not be attributed to pressure injuries. A systematic review of the literature was conducted to: (1) differentiate the types of integument injury and etiology; (2) describe the anatomic and pathophysiologic factors affecting integument failure; (3) differentiate avoidable vs. unavoidable integumentary injury of nonpressure-related sources; (4) describe factors leading to integument injury, including comorbid and risk factors; and (5) briefly discuss clinical and economic importance of delineating pressure injuries from integument failure and associated risk factors in order to determine the pathophysiology underlying wound development and multiple factors capable of interacting with pressure to synergistically influence integumentary failure. The PubMed database was searched for English-language studies during March 2020 using the key words pathophysiology, etiology, pressure ulcers, pressure injury, pressure wounds, and risk factors. The PubMed search yielded 1561 publications in total; of these, 59 were selected for review based on their relevance, timeliness, and subject matter, including 50 original studies of any study design, 5 review articles, and 4 public agency reports that addressed the 5 study purpose components. Clinicians need to better understand the pathophysiology and classification of integument injuries by underlying etiologies both avoidable and unavoidable. A more accurate diagnosis would lead to more appropriate treatment strategies, an improved quality of care for affected patients, less wasted resources and reduced financial penalties for healthcare providers, and decreased medicolegal claims.